Current trends in Mathematics Education in classrooms (Revista BOEM, 2025)
This work is the result of a qualitative research approach and characterized as a case study, which aimed to describe the current trends in mathematics education used in the classroom by teachers participating in the research in a state elementary school in the city of Tefé - AM. The theoretical framework highlights an outline of these trends to serve as a quick reference source for mathematics teachers, since it highlights pedagogical elements that can help in the classroom. The observation technique was used to collect the data, and descriptive analysis was adopted for the analysis of these data. Three elementary school mathematics teachers were observed in the classroom for two school months, and the records collected indicate that of the seven trends emphasized in the theoretical framework, four were used: playful mathematics, problem solving, mathematical investigation and digital technologies. It was noteworthy that one of the teachers, during this period, used four trends, and, in particular, in playful mathematics, explored an experimental activity to demonstrate a mathematical theorem, while the other two teachers used only one trend.
Keywords: mathematical education; current trends; teaching and learning